Assessing the impacts of extreme precipitation projections on Haihe Basin hydrology using an enhanced SWAT model - Lili Tan; Junyu Qi; Gary W. Marek; Xueliang Zhang; Jianing Ge; Danfeng Sun; Baogui Li; Puyu Feng; De Li Liu; Baoguo Li; Raghavan Srinivasan; Yong Chen (Journal of Hydrology: Regional Studies)
Study region: Haihe Basin (HB), North China. Study focus: Studying the impact of extreme precipitation on watershed hydrological factors plays a crucial role in water resource management, climate adaptation, and disaster resilience. An improved Soil and Water Assessment Tool (SWAT) was employed to assess the impact of extreme precipitation indices (EPIs) on temporal and spatial variations in hydrological factors in the HB, China. Five EPIs were identified in this study, including R10 (moderate rain), R20 (heavy rain), R50 (torrential rain), R95p (95th percentile of precipitation), and R99p (99th percentile of precipitation). New hydrological insights for the region: The EPIs with the greatest contribution rates to precipitation, water yield, and percolation in the historical period were R20 (32.1 %), R50 (14.3 %), and R20 (29.0 %), respectively, for the entire basin. During the historical period, there were more occurrences of extreme precipitation events in the plain area compared to the mountainous area. In the plain area, rainfall was beneficial for replenishing groundwater when daily precipitation exceeded 50 mm. Over the entire future period (2041–2100), R50 contributed the greatest water yield (18.4 %) and percolation (36.3 %) in the HB. Furthermore, the number of days with rainfall from 20 to 50 mm d−1 and those exceeding 50 mm d−1 increased in the future period relative to the historical period. The results of this study provide a reference for understanding the spatiotemporal distribution pattern of extreme precipitation in the HB and for relevant departments to formulate response strategies.